Pulmonary cowpox in cats: five cases. Issue 6 (June 2016) - McInerney, Jennie; Papasouliotis, Kostas; Simpson, Kerry; English, Kate; Cook, Simon; Milne, Elspeth; Gunn-Moore, Danièlle A
Case series summary: This case series documents five cases of pneumonia (with pleural effusion in three cases) caused by cowpox virus (CPxV) in domestic cats. Predisposition to pneumonia may have resulted from mixed infections in two cases (feline herpesvirus and Bordetella bronchiseptica in one cat, and Mycoplasma species in the other). Relevance and novel information: As well as diagnostic confirmation by previously described methods of virus isolation from skin lesions, and demonstration of pox virions in skin samples using electron microscopy and inclusion bodies in histological preparations, this is the first report of diagnosis by virus isolation from bronchoalveolar lavage fluid or pleural fluid, and demonstration of inclusion bodies in cytological preparations. This is also the first series to report treatment with interferon omega (IFN-ω). Two cats survived, both of which had been treated with IFN-ω. As CPxV represents a serious zoonotic risk it is an important differential diagnosis of pneumonia in cats.